PENGARUH KEPUASAN PELANGGAN DAN DIMENSI RELATIONSHIP COMMITMENT TERHADAP CUSTOMER RETENTION PADA CV TIGA SAUDARA - , Nurul Ilmi Astria; , Yulia Arisnani, MBA., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
It is important for a company to retain its customers. Company spend a higher cost to attract new customer than to retained it. The objective of this research is to find the cause of customer retention. Drawing on this framework developes several hypotheses regarding the effect of three prominent drivers on customer retention such as, customer satisfaction, calculative commitment, and affective commitment. Survey method concsist of thirteen instuments that represent each variable was use to test the hypotheses. This survey is given to customer of CV Tiga Saudara in Tangerang. The result support consistent effect of calculative commitment on retention.